Aplikasi Penyewaan Motor Pada Rental Cahaya Abadi Di Jatiasih - Yudhistira Yudhono Yudhistira (Universitas Muhammadiyah Jakarta, 2019)
ABSTRACT-The purpose of this final project is to describe the use of information systems in a company management. Data management is very important in a company, because the better management of the company will affect the survival of the company in the business world. The management of a company that does not work well causes the company to be hampered and maybe even left behind by other companies. In order to anticipate this, a work management system is integrated as a whole which is integrated into the information system. One company that currently needs this system is the Abadi Jatiasih Motor Rental which is located at the Bumi Dirgantara Permai housing block Cf2 No. 92 Jatisari, Jatiasih Bekasi. The system that has been used in this company, still uses manual methods that still require paper and storage of archives that accumulate. The system created is expected to ease and simplify the work control system in management and the data recapitulation process, therefore, the author tries to create a system that is expected to help and be made in accordance with what is needed by Abadi Abadi Motor Rental Jatiasih to serve customers in the future quickly and accuratey.